Moderasi Beragama Sebagai Instrumen Transformasi Manajemen SDM ASN: Menjawab Krisis Profesionalitas dan Korupsi - Yakobus Beda Kleden (SENTRI: Jurnal Riset Ilmiah, 2026)
Religious moderation and civil servant professionalism within Indonesia’s Ministry of Religious Affairs are complementary dimensions in building an integrity-based bureaucracy. This study addresses the controversy of religion’s role in human resource management policies amidst changing religious practices and eco-spirituality trends. The 2022 Religious Moderation and Professionalism Index (IPMB) survey revealed that around 40% of civil servants still face professionalism challenges. Using a quantitative approach based on Computer Assisted Test (CAT) IPMB results in Kupang City, the analysis shows that religious moderation has a positive and significant effect on civil servant professionalism and can serve as dan instrument for transforming religious human resource management.